PAK4 suppresses RELB to prevent senescence-like growth arrest in breast cancer - Tânia D. F. Costa (Nature Portfolio, 2019)
Oncogene induced senescence protects cells from unrestricted growth and cancer. Here, the authors show that PAK4 overrides this senescence in breast cancer cells through phosphorylation of RELB, thereby inhibiting transcription of the senescence regulator C/EBPβ.